Influence of glyphosate in the fungus trichoderma harzianum coming from rhizoctonia solani in Huancayo 2019 - Medrano De La Torre, Elsa Xiomara (2020)
The objective of this research is to determine the influence of glyphosate on the conidia count of the Trichoderma harzianum fungus grown under laboratory conditions. This fungus is found in all types of soil, but it is more important in those for agricultural use where they fulfill a beneficial function. Glyphosate is an herbicide widely used in the elimination of weeds and shrubs, its effect can be extended to beneficial fungi and its permanence in the soil exceeds the specifications in the data sheet. For this reason, the culture of T. harzianum is carried out under direct exposure with different concentrations of glyphosate, the average dose (1 ml) in the investigation arises from that recommended by the manufacturer of the product and four more are established, two major doses (1.25 ml and 1.50 ml) and two minor doses (0.50 ml and 0.75 ml). Data was collected using observation tokens. All doses were observed to decrease the number of conidia including the mean 1 ml dose producing a 54% reduction compared to the control sample. The doses of 1.25 ml and 1.50 ml reduce up to 65% and 81% respectively. Therefore, this herbicide negatively influences the growth of the fungus and consequently inhibits its beneficial actions.